Viral Infection and Apoptosis - Marc Kvansakul (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Apoptosis is a form of programmed cell death that enables the removal of damaged, infected, or otherwise unwanted cells in a controlled manner. Apoptosis can be initiated by multiple independent pathways that ultimately converge at a point where proteolytic enzymes belonging to the caspase family are activated, which dismantle the apoptotic cell. Multicellular organism have employed apoptotic mechanisms during host defence in response to viral infection to limit or prevent viral spread and replication. Consequently, viruses have evolved sophisticated molecular countermeasures to disarm host apoptotic defences, and this series of reviews and primary research articles in this Special Issue explores the intricate molecular interplay between viruses and their hosts when they battle for control of host apoptotic check-points.